Alternative procedure for the incorporation of quantum dots into poly(N‐isopropyl acrylamide‐co‐acrylic acid) microgels based on multiple interactions. Issue 13 (30th November 2015) - Cai, Yuting; Wu, Xiaoqing; Liu, Qinghao; Liu, Hongyan
ABSTRACT: Monodisperse fluorescent poly( N ‐isopropyl acrylamide‐ co ‐acrylic acid) microgels doped with quantum dots (QDs) were fabricated as follows. First, cysteamine‐capped cadmium telluride (CA–CdTe) QDs were introduced into the microgels at pH 7 by electrostatic interactions. Afterward, the CA–CdTe QDs were further immobilized in the microgels by the collapse of the polymer network when the pH of solution was adjusted to 4. In this system, there existed multiple interactions between the CA–CdTe QDs and the microgels, including hydrogen bonds, electrostatic interactions, and coordination bonds. The photoluminescence intensity and maximum emission wavelength of the resulting microgels could be easily adjusted by changes in the content of the CA–CdTe QDs in the hybrid microgels (HMs) and with differently sized QDs, respectively. We found that the lower the addition of CA–CdTe QDs was, the bigger the blueshift of the photoluminescence spectra of the HMs was and the weaker the photoluminescence intensity was. Finally, temperature‐responsive emission of the HMs was examined. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43227. Abstract :